Tribological Characteristics Comparison For Oil Palm Fibre/Epoxy And Kenaf Fibre/Epoxy Composites Under Dry Sliding Conditions - Fairuz Fazillah, Shuhimi; Mohd Fadzli, Abdollah; Md Abul, Kalam; Masjuki, Hassan; Ashafi'e, Mustafa; Hilmi, Amiruddin (Elsevier Ltd., 2016)
The aim of this study is to compare the tribological characteristics of OPF/E and KF/E composites in terms of fibre composition and temperature. A pin sample with a diameter of 10 mm was made using the hot compaction technique. The dry sliding test was performed using a pin-on-disc tribometer. Increasing the temperature resulted in increased wear and decreased friction coefficient for both composites. The mild-severe wear transition of OPF/E accelerated with fibre composition although it produced a lower wear rate than KF/E at high-temperatures. In addition, the wear mode map for both OPF/E and KF/E composites has been proposed and addressed in this paper based on wear rate values. This mild-severe wear transition has been further confirmed by worn surface morphology.